Essays on Offshoring, Wage Inequality and Innovation - Sebastian Benz (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2014)
This volume was prepared by Sebastian Benz while he was working at the Ifo Institute. It was completed in December 2013 and accepted as a doctoral thesis by the Department of Economics at the University of Munich. It includes five self-contained chapters. All chapters discuss different implications of the growing importance of trade in intermediate inputs. The first chapter compares the impact of international trade in intermediate inputs (offshoring) on wage inequality in two distinct but similar frameworks. In the first framework the profitability of offshoring is based on increasing returns to scale on the task-level, whereas the second framework relies on differences in relative factor endowments of the two countries involved in offshoring. The second chapter provides a theory of offshoring under imitation risk that explains optimal dynamic adjustments of firms' offshoring decisions and yields two new channels by which offshoring affects wage inequality. Chapter 3 studies the impact of intellectual property rights and of offshoring costs on the rate of innovation and on the offshoring intensity. In chapter 4 I estimate knowledge spillovers through outsourcing relationships between German firms, measured by the number of those firms' successful patent applications. The last chapter describes sector-level input-output relationships in eleven European economies and estimates the importance of international trade in intermediate inputs and internationally mobile capital for the interdependence of output shocks in those countries.
Keywords: C21; F11; F12; F14; F15; F16; F21; F23; F43; J31; O30; O31; O34; O52; 330; Innovation; Input-Output-Analyse; Immaterialgüterrechte; Vorleistungen; Kapitalmobilität; Einkommensverteilung; International; Wissenstransfer; Auslandsverlagerung; Outsourcing; Patent; Faktorproportionentheorem; Lohnstruktur; Trade in tasks; Auslandsverlagerung; Vorleistungen; Außenwirtschaftstheorie; Anforderungsprofil; Lohnstruktur; Imitationsstrategie; Risiko; Sachenrecht; Innovation; Wissenstransfer; Outsourcing; Theorie; Deutschland; Input-Output-Analyse; Vorleistungen; Außenhandel; Kapitalmobilität; Faktorproportionentheorem; Theorie; EU-Staaten